Analysis of Two Cephalosporin Drugs Ceftriaxone and Cefepime Alone and in Presence of Two β-Lactamase Inhibitors Sulbactam and Tazobactam - Shrestha, Bhupendra; Ranjan Bhuyan, Nihar; Nayan Sinha, Barij (Asian Journal of Chemistry, 2011)
The β-lactam is the most widely prescribed antibiotic of the all antibiotics. The most important problem related with this type of antibiotic is their susceptibility to β-lactamases which renders them ineffective. Therefore, use of inhibitors of β-lactamases that are structurally similar to β- lactam antibiotics are very much essential. In this review, the authors have extensively presented the analytical methods available for two widely used cephalosporin drugs ceftriaxone and cefepime along with two β-lactamases inhibitors sulbactam and tazobactam.